Performance improvement of handover integration of FMIPv6 in HMIPv6 - Thành, Đào Văn; Tam, Nguyễn Văn; Lợi, Vũ Duy (Journal of Computer Science and Cybernetics, 2012)
Fast handover for Hierarchical Mobile IPv6 (F-HMIPv6) is scheme that integrates Fast handovers for Mobile IPv6 (FMIPv6) in Hierarchical Mobile IPv6 (HMIPv6). F-HMIPv6 has some limitations, such as circle routing problem occurs within the handover process, packets to the destination can wrong order, the handover latency is quite high when MN moves inter-domain. We propose improved F-HMIPv6 scheme (called I-FHMIPv6) - an improvements in binding update to HA/CN when MN moves inter-domain. When a MN receives an FBAck message with the new LCoA and RCoA acceptance, it will send a Binding Update message to the HA/CN to update the MN’s new RCoA before the L2 handover occurs. So it helps avoiding circle routing problem within the handover process, can wrong order of packets at the destination and handover latency can be reduce.